Expression of Immunomodulatory Molecules PD-1, PD-L1, and PD-L2, and their Relationship With Clinicopathologic Characteristics in Endometrial Cancer. (September 2019) - Sungu, Nuran; Yildirim, Melahat; Desdicioglu, Raziye; Başaran Aydoğdu, Özge; Kiliçarslan, Aydan; Tatli Doğan, Hayriye; Kiliç Yazgan, Aylin; Akyol, Mesut; Erdoğan, Fazli
Abstract : Chemotherapeutic agents are not very effective in treating advanced endometrial cancers (ECs). Recent studies have demonstrated the immune evasion mechanism of tumors and possible remedies. Programmed cell death protein 1 (PD-1), programmed death ligand 1 (PD-L1), and programmed death ligand 2 (PD-L2) are immunomodulator molecules that have been the focus of research in lung cancer, melanoma, and renal cell cancer. However, there are few studies concerning EC. This retrospective study aimed to determine PD-1, PD-L1, and PD-L2 expression immunohistochemically in EC, and to study their correlation with clinicopathologic tumor characteristics. This study comprised 127 patients with EC. Anti PD-1, PD-L1, and PD-L2 antibodies were examined immunohistochemically on sections obtained from tissue microarray paraffin blocks. No staining with PD-1 in tumor cells was seen; however, we found positive staining in tumor cells at 36.2% with PD-L1 and 64.4% with PD-L2, and at 61.6% with PD-1, 36.2% with PD-L1, and 93.2% with PD-L2 in immune cells. When comparing staining and clinicopathologic findings, most of the PD-L1 negative tumors (both in tumor and immune cells) were FIGO Stage I, which was significantly higher than stage II-III-IV tumors ( P <0.05). There was a statistically significant association between the FIGO grade and the PD-L1 score in immune cells ( P =0.009), and between staining of PD-1, PD-L1, and PD-L2 and age ( P =0.004, 0.013, and 0.043, respectively). Interaction between PD-1, PD-L1, and PD-L2 may be a potential target for immunotherapy in elderly and advanced stage EC patients.